Electrocatalytic continuous flow chlorinations with iodine(I/III) mediators - Tuhin Patra; Sagar Arepally; Jakob Seitz; Thomas Wirth (Nature Communications, 2024)
Abstract Electrochemistry offers tunable, cost effective and environmentally friendly alternatives to carry out redox reactions with electrons as traceless reagents. The use of organoiodine compounds as electrocatalysts is largely underdeveloped, despite their widespread application as powerful and versatile reagents. Mechanistic data reveal that the hexafluoroisopropanol assisted iodoarene oxidation is followed by a stepwise chloride ligand exchange for the catalytic generation of the dichloroiodoarene mediator. Here, we report an environmentally benign iodine(I/III) electrocatalytic platform for the in situ generation of dichloroiodoarenes for different reactions such as mono- and dichlorinations as well as chlorocyclisations within a continuous flow setup.